Crisp House: social media portfolio / Fakrul Azzim Abdullah and Syazwanie Safar - Abdullah, Fakrul Azzim; Safar, Syazwanie (2022)
Crisp House is an online business that sells cassava chips from “Kerepek Tok Amin”. It is managed by two partners which are Syazwanie and Fakrul Azzim and they have three other workers. Crisp House is using a Facebook Page platform to sell and promote their products. This business wants to create a brand of quality food according to the tastes and preferences of customers. We want to preserve the Malaysian snacks in the community, especially for the youngsters. Besides that, Crisp House is selling a variety of cassava crisp in different flavours such as spicy, salted, and cheesy that can be eaten by all ages. Our chips are easy to eat and filling especially to the student who is always busy and does not have time to cook. The price of the chips is really reasonable and affordable, our range price is only from RM10 to RM13. Crisp House also provides two kinds of delivery, which is a Cash On Delivery (COD) to the customer that lives around the Melaka and the delivery fee is only from RM3 depending on the location and kilometre. We also have delivery postage to all over Malaysia including Sabah and Sarawak with the postage fee is only RM7. We set up a Facebook page to grow our small business through social media since it is easier to spread the word about our products through social media marketing. By doing so, we were also able to learn how to post for business products using teaser posts, hard sell posts, and soft sell posts. We believe that Crisp House will expand and be known in the online business in the future.